(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Sago (Metroxylon spp.) is a tropical palm plant that has a high adaptability to wet lands, swamps, and areas with abundant water availability. This article aims to analyze the potential of sago as a water source conservation plant based on various published research findings. The method used is a literature review by examining various scientific articles, books, and relevant documents that discuss the ecological characteristics, root systems, and hydrological roles of sago plants. The study results show that Sago can be categorized as an indicator plant of water sources because its distribution, growth, and productivity are highly dependent on groundwater availability and the stability of the hydrological system. The presence of sago not only indicates the existence of adequate water reserves but also contributes to maintaining the environmental hydrological function through increased infiltration, soil conservation, and catchment area maintenance. The microclimate formed within the sago stand canopy plays an important role in sustaining the water source. A dense canopy lowers air temperature, increases humidity, reduces evaporation, and enhances water infiltration into the soil. Litter and root systems increase groundwater storage capacity and support the recharge of aquifers that serve as water sources. The root system of sago has an extraordinary ability to store water through increased infiltration, formation of soil porosity, stabilization of soil structure, and maintenance of organic matter content. This ability supports the process of aquifer recharge and ensures the sustainability of water sources. Therefore, sago can be viewed as a water conservation plant that not only utilizes water resources but also actively plays a role in creating, maintaining, and protecting water sources.